Exploring the Use of Behavioural Techniques in Serious Games for Energy Efficiency: a Systematic Review and Content Analysis. - Delemere, Emma; Liston, Paul (Behavior & Social Issues, 2022)
While the efficacy of serious games for energy efficiency is well established, analysis of how such approaches employ behavioural principles has yet to be considered. This study presents a systematic review and content analysis of the use of behaviour change techniques (BCTs) within serious games for energy efficiency, defined as the use of gamification within interventions. By exploring the use of BCTs, increased understanding of the mechanisms of change underlying serious games for energy efficiency can be obtained. Using search terms relating to (1) serious games and (2) energy efficiency, seven databases were searched. Content analysis was completed using the behaviour change taxonomy v1 (BCTv1; Michie et al., Annals of Behavioral Medicine, 46(1), 81–95, 2013). Twenty-one studies met inclusion criteria. Serious games targeted residential (n = 10), commercial (n = 8), educational (n = 1), and public (n = 2) settings. Average decreases in energy use of 15.2% in residential settings, 18.4% in commercial settings and 9.9% in educational and public settings were found. Across serious games, 36 individual BCTs were found with an average of 9.45 individual BCTs per game. Common BCTs included monitoring of behaviour by others without feedback (n = 18), feedback on behaviour (n = 17) and self-monitoring of behaviour (n = 12). Results highlight the positive impacts of serious games on energy consumption behaviour and demonstrate the utility of BCTs within such games. Opportunities exist to further enhance the efficacy of serious games through better leveraging behavioural techniques using knowledge from behaviour analysis. Behaviour analysts should consider serious games when developing interventions to support energy behaviour change.